Guest

Please answer the question no 3 as soon as possible thanks

Please answer the question no 3 as soon as possible thanks

Question Image
Grade:11

1 Answers

Arun
25763 Points
4 years ago
Dear Chandan
P1 = P
P2 = 4P/3
y = 3/2
Now
P1 * (V1)^(3/2) = P2 * (V2)^(3/2)
Hope now you can do this
Regards
Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free